Getting to Yes with China in Cyberspace - Harold, Scott Warren; Libicki, Martin C.; Cevallos, Astrid Stuth (RAND Corporation, 2023)
This study explores U.S. policy options for managing cyberspace relations with China via agreements and norms of behavior. It considers two questions: Can negotiations lead to meaningful agreement on norms? If so, what does each side need to be prepared to exchange in order to achieve an acceptable outcome? This analysis should interest those concerned with U.S.-China relations and with developing norms of conduct in cyberspace.